Discount propaganda on Tiktok live features as a means of @somethincofficial in increasing sales - Farida Nurfalah; Dea Refani Sapitri; Erick Satyawijaya (Interdisciplinary Social Studies, 2024)
The development of technology has made many social media a means to channel information and communication. The media that is currently often used by the public is TikTok. Indonesia is the second largest market in the world for TikTok users in 2023 with 106.52 million active users. The type of research used by the researcher is qualitative descriptive, data collection techniques using observation and interview methods, book literature, scientific journals, and interviews with 5 adolescent informants of TikTok followers Somethinc in Cirebon City. With its proven quality, as well as the delivery of messages through promotions, Somethinc has succeeded in building brand awareness among teenagers in Cirebon City so that its products are liked and in great demand. TikTok social media as a means of attracting buying interest is because of its attractive content accompanied by influencer support that helps the process of delivering the message desired by business actors, as well as the existence of a live shopping feature that makes the audience interested in buying because of the many promos, free shipping fees and discounts obtained as well as live chat interactions that make it easier for consumers to solve their problems. TikTok social media is a strategic media as a means of promotion in attracting interest in buying Somethinc products. This is due to the attention of consumers in the form of informative content, on TikTok social media there are many attractive promos that make consumers interested in buying, and there is a message feature in TikTok social media that makes it easier for consumers to interact with business actors directly with the aim of getting solutions to obstacles.